PENGEMBANGAN INDUSTRI CRUDE PALM OIL BERKELANJUTAN DENGAN MENGGUNAKAN MODEL GEO-SPATIAL MULTICRITERIA DECISION ANALYSIS - I Ketut Gunarta (Bumi Lestari Journal of Environment, 2013)
AbstractDevelopment of crude palm oil industry in Indonesia and Malaysia have been able tochange the map of world vegetable oil in a short time. In 1985, Indonesia palm oil productionreached 1.3 million tons. However, in 2007 Indonesia has surpassed the total production ofCPO Malaysia. Indonesia’s CPO total production in 2011is 23 million tons. To producethat amount of production volume, there are at least 4 million ha of land to produce rawmaterial for the factory. With the next target of 50 million tons of production will of coursebe a lot of land to be prepared or converted. However, the increasing of CPO production isnot always have a positive impact. Forest damage caused by the opening of oil palmplantation and is still a lack of consideration to increase CPO production through increasedproductivity of the land received many responses from various parties environmentalists.Approximately 400,000 ha of forests in Indonesia per year be converted into oil palmplantations. The use of forest land for oil palm plantations is one of the growing threat ofIndonesia’s CPO production so necessary to control the development of this industry.Thispaper provides an alternative optimal solution to the development of palm oil industry bybuilding a decision support system that integrates GIS with spatial analysis modelsesspecially multicriteria decision making. This spatial based decision support system has acapability to accommodate the limitations of land development, environmental constraints,transportation facilities and transportation networks as well to get the optimal CPO industrydevelopment decision.